2020
DOI: 10.1016/j.fertnstert.2020.02.048
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Recombinant HCG Pretreatment on Surgical Sperm Retrieval Rates in Patients With Non-Obstructive Azoospermia – An Audit of Our Practice

Abstract: significantly associated with older maternal age (R¼-0.27, p<0.01), fewer 2PNs, higher aneuploidy rate, and fewer usable embryos for transfer. (Table 1)However, when controlling for maternal age using multivariate regression analysis, AMH was not an independent predictor of the rate of aneuploid embryos (p¼0.11) CONCLUSIONS: AMH is an established marker of ovarian reserve and is predictive of the number of embryos available for biopsy, however our results suggest that it is not an independent predictor of blas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Finally, when the only study not published as a full text ( Sen et al , 2020 ) was excluded, there was a non-statistically significant trend towards a higher SSR in the normogonadotropic group compared to the hypergonadotropic cohort (OR 1.9, 95% CI: 0.95–3.78, P = 0.07).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Finally, when the only study not published as a full text ( Sen et al , 2020 ) was excluded, there was a non-statistically significant trend towards a higher SSR in the normogonadotropic group compared to the hypergonadotropic cohort (OR 1.9, 95% CI: 0.95–3.78, P = 0.07).…”
Section: Resultsmentioning
confidence: 94%
“…Of the retrieved texts, we analysed 10 studies ( Tables I and II ). Among them, five studies ( Reifsnyder et al , 2012 ; Shiraishi et al , 2012 ; Majzoub et al , 2016 ; Hu et al , 2018 ; Amer et al , 2020 ) included hypergonadotropic subjects whereas five ( Aydos et al , 2003 ; Hussein et al , 2013 ; Gul, 2016 ; Cocci et al , 2018 ; Sen et al , 2020 ) included normogonadotropic men. The characteristics of the retrieved studies are reported in Tables I and II .…”
Section: Resultsmentioning
confidence: 99%